Bacteriophages: A Challenge for Antimicrobial Therapy - Nallelyt Segundo-Arizmendi; Dafne Arellano-Maciel; Abraham Rivera-Ramírez; Adán Manuel Piña-González; Gamaliel López-Leal; Efren Hernández-Baltazar (Microorganisms)
Phage therapy, which involves the use of bacteriophages (phages) to combat bacterial infections, is emerging as a promising approach to address the escalating threat posed by multidrug-resistant (MDR) bacteria. This brief review examines the historical background and recent advancements in phage research, focusing on their genomics, interactions with host bacteria, and progress in medical and biotechnological applications. Additionally, we expose key aspects of the mechanisms of action, and therapeutic uses of phage considerations in treating MDR bacterial infections are discussed, particularly in the context of infections related to virus–bacteria interactions.